It Related Vocabulary Development and Some Obstacles in Teaching Foreign Language in Technical Universities - Shakhakimova Mavjuda Tashpolatovna; Ibragimova Shakhnoza Turgunovna (Zien Journals, 2021)
The purpose of this article is to consider some common difficulties encountered in development and teaching vocabulary in technical higher educational institutions. It deals with the problem of acquisition of IT related vocabulary by students in the foreign language teaching process. There have been analyzed some problems in teaching a foreign language to learners of a technical higher establishment. There are some recommendations for teachers in creating a program of explicit IT related vocabulary instruction to motivate their students to learn and master a foreign language through learning terminology
Keywords: IT related vocabulary; communicativeness; semantics; definition